Tindak Tutur Ilokusi Ekspresif Perceraian "Irish Ammar " Pada Kolom Komentar Instagram Lambe Turah: Kajian Pragmatik - Haris, Aulia; Amri, Yusni Khairul (Jurnal Hata Poda, 2023)
This research describes the characteristics, form and purpose of action spoken in Indonesian used on social media. MomentNowadays, almost all Indonesian people have turned to the media social, including Instagram. This research aims to conductanalysis of expressive illocutionary speech acts in the Instagram comment column Lambe Turah regarding the news of Ireland's divorce from Ammar with The pragmatic study approach uses qualitative descriptive methods.Data collection techniques use observation and documentation Note. Expressive Illocutionary Speech Acts are often found in columns comments on Lambe turah's Instagram account. Based on speech act theoryThere are seven illocutionary expressions proposed by Searle (1979), expressive speech acts, namely, happy, sad, praising, reassuring,criticism, and hope. Keywords: Expressive Speech Acts, Instagram